Unusual Presentation of a Rare Disease: A Case Report of Fungal Necrotizing Otitis Media and Mastoiditis - Ermia Mousavi Mohammadi; Mohsen Rajati; Hossein Zarrinfar (Clinical Case Reports)
ABSTRACT Acute necrotizing otitis media is a severe middle ear infection which causes necrosis of the tympanic cavity. A 54‐year‐old female was presented who suffered from diabetes mellitus and end‐stage renal disease presenting with severe otalgia, initially thought to be necrotizing otitis externa. She rapidly progressed to total necrosis of the tympanic membrane. Further assessments confirmed a fungal disease caused by Candida tropicalis and Aspergillus flavus. Immediate antifungal therapy with amphotericin B and subsequent radical mastoidectomy managed to control the disease with no sign of necrosis after 3 months. Early diagnosis, aggressive systemic antifungal treatment, and surgical debridement are vital components for successful management of such cases.